Dynamics of a Delayed Model for the Transmission of Malicious Objects in Computer Network - Zizhen Zhang; Huizhong Yang (The Scientific World Journal)
An SEIQRS model for the transmission of malicious objects in computer network with two delays is investigated in this paper. We show that possible combination of the two delays can affect the stability of the model and make the model bifurcate periodic solutions under some certain conditions. For further investigation, properties of the periodic solutions are studied by using the normal form method and center manifold theory. Finally, some numerical simulations are given to justify the theoretical results.